Integral evaluation of hemodynamic performance of students in the initial stage of adaptation to the educational process (Eurasian Journal of Ecology, 2016)
The article presents data on the study of the functional capacity of the cardiovascular system of the body adapting to the educational process undergraduate courses to assess the physiological reserve capacity of the circulatory system.
Keywords: haemo dynamics; systolic pressure; diastolic pressure; systolic volume of blood; minute volume of blood